Strengthening Students' Self-Reliance Values through Islamic Boarding School Education Strategies During the Global Health Crisis - Sadiah, Dewi; Mustofa, Mustofa (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to describe the educational development strategies in fostering student independence at Darussalam Islamic Boarding School, MAN 1 Ciamis during the Covid-19 pandemic. As the oldest of Islamic education in Indonesia, pesantren faced a dual challenge: maintaining the continuity of character education while ensuring the health and safety of students. A descriptive-analytical method with a qualitative approach was employed. Data were collected through observation, interviews, and documentation. The findings show that leaders and religious teachers fostered independence by habituating students to daily religious and educational activities, such as congregational prayers, recitations, self-reliance tasks, and instilling religious values. The learning objectives targeted students' responsibility, discipline, initiative, and integrity. Teaching methods included sorogan, bandungan, lectures, discussions, modeling, habituation, and the use of rewards and punishments. During the pandemic, the school formed an internal task force to maintain health protocols. As a result, students demonstrated positive changes, including improved independence, discipline, learning motivation, and environmental awareness. The study recommends strengthening religious routines and active mentor involvement to support student independence in the new normal era. Penelitian ini bertujuan untuk mendeskripsikan strategi pengembangan pendidikan pesantren dalam membina kemandirian santri di Pondok Pesantren Darussalam MAN 1 Ciamis selama masa pandemi Covid-19. Pesantren sebagai lembaga pendidikan Islam tertua di Indonesia memiliki tantangan ganda, yaitu mempertahankan keberlangsungan pendidikan karakter sambil memastikan kesehatan santri Metode yang digunakan adalah deskriptif-analitik dengan pendekatan kualitatif. Data diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pimpinan dan guru agama menerapkan pembinaan kemandirian santri melalui pembiasaan kegiatan harian seperti shalat berjamaah, pengajian, tugas mandiri, serta penerapan nilai-nilai religius dalam kehidupan sehari-hari. Tujuan pembelajaran diarahkan agar santri mampu bertanggung jawab terhadap diri sendiri, memiliki inisiatif, kedisiplinan, dan integritas dalam menjalani kehidupan. Metode pembelajaran yang digunakan antara lain: sorogan, bandungan, ceramah, diskusi, keteladanan, habituasi, serta reward dan punishment. Di masa pandemi, pesantren juga membentuk gugus tugas internal untuk menjaga protokol kesehatan. Hasilnya, santri menunjukkan perubahan positif berupa peningkatan kemandirian, kedisiplinan, motivasi belajar, dan kepedulian terhadap lingkungan. Penelitian ini merekomendasikan penguatan pembiasaan religius dan keterlibatan aktif pembimbing untuk mendukung kemandirian santri di masa adaptasi kebiasaan baru.